Brainstem metabotropic glutamate receptors reduce food intake and activate dorsal pontine and medullar structures after peripheral bacterial lipopolysaccharide administration. (August 2016) - Chaskiel, Léa; Paul, Flora; Gerstberger, Rüdiger; Hübschle, Thomas; Konsman, Jan Pieter
Abstract: During infection-induced inflammation food intake is reduced. Vagal and brainstem pathways are important both in feeding regulation and immune-to-brain communication. Glutamate is released by vagal afferent terminals in the nucleus of the solitary tract and by its neurons projecting to the parabrachial nuclei. We therefore studied the role of brainstem glutamate receptors in spontaneous food intake of healthy animals and during sickness-associated hypophagia after peripheral administration of bacterial lipopolysaccharides or interleukin-1beta. Brainstem group I and II metabotropic, but not ionotropic, glutamate receptor antagonism increased food intake both in saline- and lipopolysaccharide-treated rats. In these animals, expression of the cellular activation marker c-Fos in the lateral parabrachial nuclei and lipopolysaccharide-induced activation of the nucleus of the solitary tract rostral to the area postrema were suppressed. Group I metabotropic glutamate receptors did not colocalize with c-Fos or neurons regulating gastric function in these structures. Group I metabotropic glutamate receptors were, however, found on raphé magnus neurons that were part of the brainstem circuit innervating the stomach and on trigeminal and hypoglossal motor neurons. In conclusion, our findings show that brainstem metabotropic glutamate receptors reduce food intake and activate the lateral parabrachial nuclei as well as the rostral nucleus of the solitary tract after peripheral bacterial lipopolysaccharide administration. They also provide insight into potential group I metabotropic glutamate receptor-dependent brainstem circuits mediating these effects. Highlights: Metabotropic glutamate receptors reduce food intake in saline- and LPS-treated rats. Parabrachial c-Fos expression depends on metabotropic glutamate receptors. Rostral NTS LPS-induced c-Fos depends on metabotropic glutamate receptors. LPS-induced c-Fos-positive cells do not express metabotropic glutamate receptors. Raphé neurons regulating gastric output express metabotropic glutamate receptors.